Therapeutic relationship between nurse and family based on the theory of Joyce Travelbee, in a hospital in Lima: Relación terapéutica entre enfermera y familia basada en la teoría de Joyce Travelbee, en un hospital de Lima - Jahuancama Villagaray, Olga Liz (2017)
OBJECTIVES: To describe the characteristics of the therapeutic relationship according to the Joyce Travelbee theory between nurse and family of patients hospitalized in emergency services of a hospital in Lima. MATERIALS AND METHODS: Descriptive and transversal, 60 family members participated, a perception survey was applied with Likert scale. RESULTS: According to Joyce Travelbee’s theory, the therapeutic relationship between the nurse and the family is considered positive for 58,3% of the relatives. For 41, 7% of this, the relationship is acceptable, and for 16% is positive. On the other hand, 41,6% considers this kind of relationship negative. 38,3 % of this considers not too acceptable, and 3,3%considers it negative. The therapeutic relationship between nurse and family, according to the dimensions, phases or stages established by Joyce Travelbee, are five. This relationship is appreciated in a positive way, especially in the phase of transfer in 75% of families, the phase of empathy in 51% of families. However, it is considered negative according to the order of priority in the phase of emergent identities in 59,5% of families, in the phase of original encounter in 55,9% of families, and in the phase of compassion in 53,1% of families. CONCLUSIONS: The interpersonal relationship between nurse and family is positive. The empathy and transfer phases are considered positive while the original encounter phases, emergent identities and compassion are considered as negative.